Varahikanda as a Fifth Medhya Rasayana w.s.r to Indu (AYUSHDHARA, 2024)
Traditional medicine is a group of different medical practices being practiced in 170 countries around the globe according to World Health Organisation. Ayurveda system of medicine also comes under traditional medicine according to WHO. Knowledge of Ayurveda is passed on from generation to generation through observation and practices over centuries. Various controversies arise in identification of some herbs mentioned in Ayurvedic texts and at the same time some important karma of a known medicinal substance becomes obliterated due to ignorance. Medhya rasayana is a very famous concept first given in Charaka Samhita Rasayana adhikara[1] followed by Vagabhata in Ashtanga sangraha and Ashtanga hridaya. It consists of four intellect promoting herbs viz., Mandukaparni, yashtimadhu, Guduchi and Shankhapushpi. A term Sahamulapushpi that appears in the original verse is understood in different manner by different Acharyas. Indu the commentator of Ashtanga hridaya commented Sahamulapushpi as a synonym of Varahikanda and counted it as fifth Medhya rasayana drug. Varahikanda is a famous Balya herb that is botanically identified as (Diascorea bulbifera L.) of the family Diascoreaceae. References of the drug are mentioned in Brihattrayi and it has been discussed widely in Nighantus as well. Varahikanda has mainly Balya (strength promoting), Vrushya (aphrodisiac), Rasayana (rejuvenative) properties. This review mainly empha